2008
DOI: 10.1088/0953-8984/20/46/465210
|View full text |Cite
|
Sign up to set email alerts
|

Titanium and native defects in LiBH4and NaAlH4

Abstract: We report combined density functional studies and thermodynamic considerations on Ti-related and native defects in lithium borohydride and sodium alanate. Ti atoms introduced into the bulk of LiBH(4) are thermodynamically unfavorable for all their oxidation states, while high oxidation states of Ti(n+) cations may become thermodynamically stable in the bulk of NaAlH(4) at certain thermodynamic conditions. Neutral hydrogen vacancies and interstitials or cation vacancies are less stable than their charged counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
2
31
1
1
Order By: Relevance
“…Interestingly, the sorption reaction is only reversible under technically applicable conditions, if the material is doped with transition-metal compounds, most efficiently with titanium compounds [68][69][70]. A multitude of experimental and theoretical methods have been applied to unravel the mechanism of the formation and decomposition process of NaAlH 4 -so far without a conclusive model [71][72][73][74][75][76][77][78][79][80][81]. Furthermore, similar effective additives for other complex hydrides e.g.…”
Section: Sorption Mechanism Of Complex Hydrides Probed By Vibrationalmentioning
confidence: 99%
“…Interestingly, the sorption reaction is only reversible under technically applicable conditions, if the material is doped with transition-metal compounds, most efficiently with titanium compounds [68][69][70]. A multitude of experimental and theoretical methods have been applied to unravel the mechanism of the formation and decomposition process of NaAlH 4 -so far without a conclusive model [71][72][73][74][75][76][77][78][79][80][81]. Furthermore, similar effective additives for other complex hydrides e.g.…”
Section: Sorption Mechanism Of Complex Hydrides Probed By Vibrationalmentioning
confidence: 99%
“…However because of no change of the limiting rate neither for hydrogen absorption (contracting volume model) nor for desorption (interfaced-controlled one-dimensional growth) [8], induced by the additives, the latter do not show catalytic behavior. The theoretical work [9] has shown that thermodynamic stability of point defects in complex hydrides deÞnes the ground or inter-mediate states or the driving force for atomic motion. Incor-poration of Ti cations in LiBH 4 is energetically unfavorable suggesting that only surface effect takes place.…”
Section: Introductionmentioning
confidence: 99%
“…In case of RHCs, based on lithium borohydride, the nium additives on hydrogen sorption of LiHeMgB2 composite additives likely react with LiBH4 in similar way. However, in order to Þnd suitable chemical structure and optimal MgH2 plays an additional role in the kinetic improvement [9]. amount of the proposed dopant.…”
mentioning
confidence: 99%
“…Previous calculations have addressed the energetics of defects in NaAlH 4 using static total energies as obtained from density-functional theory (DFT) calculations. 24,30 We go beyond these studies by incorporating finite-temperature vibrational free energies and the free energy of gaseous hydrogen. We also present DFT calculations of defects in Na 3 AlH 6 , a product phase of Reaction 1, which to the best of our knowledge have not been previously published.…”
Section: ' Introductionmentioning
confidence: 99%